Kepemimpinan Kepala Sekolah Perempuan Dalam Meningkatkan Kualitas Pendidikan di PAUD Kusuma Indonesia Kaloran Temanggung - Eva Indrayani; Nina Oktarina; Fathur Rokhman (Universitas 17 Agustus 1945 Semarang, 2024)
This article describes a descriptive qualitative research on the transformational leadership of female school principals in improving the quality of education at PAUD Kusuma Indonesia. This research was conducted through observation, interviews and documentation studies. The main problem faced is the challenge in implementing effective transformational leadership practices. The aim of this research is to understand how transformational leadership can be applied by female school principals to improve the quality of education in PAUD. The main results show that female school principals are able to carry out effective transformational leadership practices, which are reflected in increasing staff motivation and performance, as well as improving the quality of learning and the learning environment in PAUD. The conclusion of this research is that transformational leadership by female school principals has a significant role in improving the quality of education in PAUD, and greater support from related parties is needed to strengthen this practice.